TINJAUAN PROSEDUR AUDIT ATAS KAS KECIL PADA KANTOR AKUNTAN PUBLIK HELIANTONO DAN REKAN - Juvita Maharani, (2023)
Petty Cash has an important role for the financial statements of a company. Hence the importance of auditing cash to become relevant and reliable data. The purpose of this final project is to find out the stages in auditing the petty cash of a company or entity. Several stages of the process in auditing petty cash also must understand the method used and process the data first. In auditing petty cash, calculating physical money is carried out by the auditor and supervised by the employee who is responsible for the company's cashier so that the cash audit will result in whether the company's balance is reliable and adequate.